Phosphatase of Regenerating Liver-1 (PRL-1)-Overexpressing Placenta-Derived Mesenchymal Stem Cells Enhance Antioxidant Effects via Peroxiredoxin 3 in TAA-Injured Rat Livers - Hee Jung Park; Ji Hye Jun; Jae Yeon Kim; Hye Jung Jang; Ja-Yun Lim; Si Hyun Bae; Gi Jin Kim (MDPI AG, 2022)
DNA damage repair is induced by several factors and is critical for cell survival, and many cellular DNA damage repair mechanisms are closely linked. Antioxidant enzymes that control cytokine-induced peroxide levels, such as peroxiredoxins (Prxs) and catalase (CAT), are involved in DNA repair systems. We previously demonstrated that placenta-derived mesenchymal stem cells (PD-MSCs) that overexpress PRL-1 (PRL-1(+)) promote liver regeneration via antioxidant effects in TAA-injured livers. However, the efficacy of these cells in regeneration and the role of Prxs in their DNA repair system have not been reported. Therefore, our objective was to analyze the Prx-based DNA repair mechanism in naïve or PRL-1(+)-transplanted TAA-injured rat livers. Apoptotic cell numbers were significantly decreased in the PRL-1(+) transplantation group versus the nontransplantation (NTx) group (p < 0.05). The expression of antioxidant markers was significantly increased in PRL-1(+) cells compared to NTx cells (p < 0.05). MitoSOX and Prx3 demonstrated a significant negative correlation coefficient (R2 = −0.8123). Furthermore, DNA damage marker levels were significantly decreased in PRL-1(+) cells compared to NTx cells (p < 0.05). In conclusion, increased Prx3 levels in PRL-1(+) cells result in an effective antioxidant effect in TAA-injured liver disease, and Prx3 is also involved in repairing damaged DNA.